Efficacy and Complications of Microsurgical Neurovascular Decompression in 55 Patients With Hemifacial Spasm. (17th November 2020) - Compagnon, Chloé; Labrousse, Marc; Brenet, Esteban; Chays, André; Bazin, Arnaud; Kleiber, Jean‐Charles; Dubernard, Xavier
Abstract : Objective: To analyze the efficacy and complications of microvascular decompression for hemifacial spasm. Study Design: Retrospective study. Setting: Regional hospital. Methods: Fifty‐five patients with hemifacial spasm were treated by microvascular decompression. All patients with hemifacial spasm who underwent retrosigmoid microvascular decompression from May 2004 to January 2017 were included. Patients with no conflict on preoperative magnetic resonance imaging or with an alternate diagnosis were excluded. Results: The overall cure rate was 83.64%, with an average follow‐up of 7.4 years. A left‐sided hemifacial spasm was a healing‐promoting factor ( P =. 01). The median healing was 0.03 months, and the mean was 6 months. The efficacy remained high in the medium term (88% at 3 years), long term (90.24% at 5 years), and very long term (90.48% at 8 years). The recurrence rate was 9.8%. Favorable criteria included a right‐sided spasm ( P =. 01) and an average age of 62 years ( P =. 03). The specific complications were permanent facial palsy (3.63%), unilateral deafness (5.45%), and hearing loss (3.63%). No death was reported. Regarding the quality of life of the patients, 94.7% had a modified HFS‐8 postoperative score of 0 (Hemifacial Spasm 8 Quality of Life Scale). Conclusion: Microvascular decompression for hemifacial spasm is an effective and lasting technique. Its low rate of complications and the considerable quality‐of‐life improvement should lead surgeons to propose it to patients as soon as botulinum toxin injections become ineffective or poorly tolerated.